Nursing of integrated traditional Chinese and Western medicine in a case of severe diabetic ketoacidosis complicated with intestinal obstruction and pneumonia caused by immunotherapy for gastric cancer (1例胃癌免疫治疗引起重度糖尿病酮症酸中毒伴肠梗阻并发肺炎的中西医结合护理体会) - LIU Yin (柳吟); HUANG Jun (黄君); QIU Minyan (邱敏燕); ZHAO Hongxia (赵红霞); SHEN Xiaoyan (沈晓燕) (Journal of International Translational Medicine Limited, 2024)
This paper summarized the integrated traditional Chinese and Western medicine nursing of a case of severe diabetic ketoacidosis (DKA) with acute intestinal obstruction complicated with pneumonia secondary to gastric adenocarcinoma treated with anti-PD-1. The main points of nursing included: disease monitoring, nausea and vomiting nursing, lack of knowledge and other general nursing measures. The key and difficult points of nursing for this case were complicated with intestinal obstruction and ICPis related diabetes. Therefore, integrated traditional Chinese and western medicine nursing and corresponding nursing measures were taken to relieve the clinical symptoms and improve the rehabilitation of the patient. (本文总结1例基于胃癌免疫治疗引起重度糖尿病酮症酸中毒(DKA)伴肠梗阻并发肺炎患者的中西医结合护理经验。患者病情复杂, 合并症多, 在加强病情监测、心理护理、恶心呕吐护理、健康宣教等常规护理的基础上, 针对并发症采取肠梗阻护理干预、DKA急性发作期护理干预, 改善患者症状, 促进患者早期康复。)